(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurship has gained more importance as it fulfils the gap in the existing market by focusing on small needs and desire of customer and the market. The government has also initiated this momentum by developing policy initiative to promote entrepreneurs and develop entrepreneurial skills by passing favourable plans to strengthen the entrepreneurial ecosystem in the country. Today every field has been captured by women, from home to defence. Entrepreneurial field is also no exception. Women entrepreneurship can bring transformational change in the society by adding to the country’s economy as well as their home economy. One of the practical solutions of solving unemployment issues is women entrepreneurship. According to National Statistical Office (NSO) data, female literacy rate stands at 70.30% in the year 2021.However, the relationship of literacy and entrepreneurship has no positive corelation. Even illiterate women venture into entrepreneurship field. The present paper tries to study the role of women entrepreneur in accelerating the growth of small-scale industries in Indian economy and also reveals the challenges faced in this sector.